FEATURES OF EDUCATION IN THE DEVELOPMENT OF NEW UZBEKISTAN (American Journal of Interdisciplinary Research and Development, 2022)
The article scientifically substantiates the issues of education in the development of New Uzbekistan. As a result of large-scale reforms and creative work carried out in our country, the way of thinking and worldview of our people is changing. In our country, the importance of the life-giving idea «From national revival to national upsurge» in the development of the rule of law and civil society is growing.